2022
DOI: 10.1007/s10802-022-00911-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Maternal Stressful Life Events and Perceived Distress during Pregnancy and Child Mental Health at Age 4

Abstract: Accumulating evidence suggests that maternal exposure to objectively stressful events and subjective distress during pregnancy may have intergenerational impacts on children’s mental health, yet evidence is limited. In a multisite longitudinal cohort (N = 454), we used multi-variable linear regression models to evaluate the predictive value of exposure to stressful events and perceived distress in pregnancy for children’s internalizing problems, externalizing problems, and adaptive skills at age 4. We also exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Though this body of work is compelling, with some exceptions, most studies have focused on outcomes in young children and relied on parent reports, raising concerns about time-limited programming effects and potential rater bias in tested associations (De Los Reyes et al, 2015). In addition, despite evidence that maternal exposure to major life events during pregnancy is associated with child outcomes, even after adjusting for maternal subjective ratings of psychological distress during pregnancy (Rudd et al, 2022), most studies have relied on maternal self-report of subjective distress rather than more objective accounts of stressor exposures.…”
Section: Maternal Exposure To Stress During Pregnancy and Offspring I...mentioning
confidence: 99%
“…Though this body of work is compelling, with some exceptions, most studies have focused on outcomes in young children and relied on parent reports, raising concerns about time-limited programming effects and potential rater bias in tested associations (De Los Reyes et al, 2015). In addition, despite evidence that maternal exposure to major life events during pregnancy is associated with child outcomes, even after adjusting for maternal subjective ratings of psychological distress during pregnancy (Rudd et al, 2022), most studies have relied on maternal self-report of subjective distress rather than more objective accounts of stressor exposures.…”
Section: Maternal Exposure To Stress During Pregnancy and Offspring I...mentioning
confidence: 99%
“…There is some evidence that boys might be more likely to develop externalizing problems during childhood within the context of maternal prenatal stress ( 40 , 48 , 49 ). Yet, findings here are still mixed, and fewer studies have examined these potential sex differences in early childhood, when externalizing problems are less sex differentiated ( 43 , 47 , 50 ).…”
Section: Intergenerational Transmission Of Effects Of Women's Stresso...mentioning
confidence: 84%
“…There is evidence regarding differential sex effects of maternal stress on offspring psychopathology; however, to date these findings have been quite mixed—necessitating additional inquiry ( 17 , 33 , 40 43 ). This is particularly important to examine in outcomes with well-established sex differences, such as externalizing behavior problems during childhood.…”
Section: Intergenerational Transmission Of Effects Of Women's Stresso...mentioning
confidence: 99%
“…In ECHO-PATHWAYS analyses focused on the TIDES cohort, we found that prenatal phthalate exposure was associated with child behaviours as well as social responsiveness at age 4–6 in a sex-specific manner, indicating that phthalates may have sex-specific impacts on child behaviour and development 65. Additional work in TIDES demonstrated that maternal stressful life events and distress during pregnancy were associated with more child behaviour problems and lower levels of adaptive functioning 66. Since GAPPS-PW had been a closed cohort, no child health data was available until ECHO-PATHWAYS began and therefore no child health analyses using extant data could be leveraged within this cohort.…”
Section: Introductionmentioning
confidence: 79%
“… 65 Additional work in TIDES demonstrated that maternal stressful life events and distress during pregnancy were associated with more child behaviour problems and lower levels of adaptive functioning. 66 Since GAPPS-PW had been a closed cohort, no child health data was available until ECHO-PATHWAYS began and therefore no child health analyses using extant data could be leveraged within this cohort. Currently, GAPPS-PW has collected data on over 600 ECHO-PATHWAYS participants, and consortium analyses including these data are ongoing.…”
Section: Introductionmentioning
confidence: 99%